Cardiorespiratory responses to maximal arm and leg exercise in national-class marathon runners - de Jong, A. T.; Bonzheim, K.; Franklin, B. A.; Saltarelli, W. (The Physician and Sportsmedicine, 2009)
Marathon runners (MR) are among the most aerobically fit athletes in the world. Although aerobic capacity (VO2max) during arm exercise generally varies between 64% and 80% of leg VO2max (mean 70%) in healthy men, few data are available regarding the comparative arm fitness of MR. To clarify the relationship between arm and leg fitness in MR, we studied 10 national-class MR (mean ± standard deviation age 30 ± 4 years) whose best marathon times averaged < 2 hours and 40 minutes. Each MR underwent lower and upper body maximal exercise evaluations with measurement of cardiorespiratory variables using indirect calorimetry during treadmill testing (standard Bruce protocol) and arm-crank ergometry, respectively. Our subjects achieved VO2max levels equaling 75.8 ± 7.1 mL/kg/min (5.2 ± 0.6 L/min) during treadmill testing, which was significantly higher than the level of cardiorespiratory fitness achieved during maximal arm exercise (45.4 ± 12.4 mL/kg/min [3.1 ± 0.9 L/min]; P < 0.01). In addition, maximal heart rate (183.2 ± 8.2 vs 163.7 ± 10 bpm) and systolic blood pressure (201.8 ± 10.1 vs 186.6 ± 12.1 mm Hg) were significantly higher (P < 0.01 and P < 0.05, respectively) during maximal leg versus arm exercise. Relative arm fitness (arm VO2max/leg VO2max) was extremely variable (41%-76%), averaging 60% ± 13%. Although MR are able to achieve significantly higher VO2max values during treadmill testing than those observed in the general population, their relative arm fitness appears to be slightly reduced. These findings add to and strongly support the specificity of measurement and training concept.